Autogenic spinal excitatory circuit ensures skilled hand movements in primates - GeeHee Kim; Saeka Tomatsu; Tatsuya Umeda; Tomohiko Takei; Tetsuro Funato; Kazuhiko Seki (Proceedings of the National Academy of Sciences, 2026)
Skillful hand movements are a hallmark of primates, including humans, requiring sophisticated motor planning and execution. Building on the well-established cortical basis of dexterous control, our findings show that spinal excitatory reflex circuits form a critical complementary pathway that contributes substantially to the planning and execution of skillful hand movements. Using a combination of experimental approaches with behaving nonhuman primates and predictive simulation, we identified a group of excitatory spinal interneurons that orchestrate a closed-loop, positive feedback mechanism during voluntary wrist movements. This mechanism is characterized by a bidirectional interaction between interneuronal spiking and muscle activity, mediated by motoneuronal efferent signals and proprioceptive afferent signals from the same agonistic muscles. Furthermore, we demonstrate that the temporal profile of muscle activity during movement execution, including amplitude and duration, is predetermined during motor planning at the spinal interneurons, functioning as a force-feedback gain within the excitatory circuit. These findings suggest that autogenic, Ib spinal excitatory circuits play a predominant role in shaping overall muscle activation during motor execution, provided the proper reflex gain is preset by higher neural systems during motor planning. Together, our findings provide cellular-level evidence that spinal reflex loops operate in parallel with cortical mechanisms to support skilled voluntary movements in primates.